2020
DOI: 10.1167/iovs.61.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hyaluronan Synthesis Inhibition by 4-Methylumbelliferone in Orbital Fibroblasts

Abstract: PURPOSE. Hyaluronan (HA) overproduction by orbital fibroblasts (OFs) is a major factor in the pathogenesis of Graves' orbitopathy (GO). 4-methylumbelliferone (4-MU) is an inhibitor of HA synthesis in different cell types in vitro and has beneficial effects in animal models of autoimmune diseases. METHODS. HA production and mRNA expression of HA synthases (HAS1, HAS2, and HAS3) and hyaluronidases (HYAL1 and HYAL2) were measured in the presence and absence of 4-MU in unstimulated and transforming growth factor-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…2019). Previous work has shown that 4-MU inhibits the production of UDP-glucuronic acid (UDP-GlcA) (Galgoczi et al . 2020), a key substrate for HA production, and the expression of hyaluronan synthases (HASs), UDP-glucose-pyrophosphorylase (an enzyme for the biosynthesis of UDP-glucose) and UDP-glucose-dehydrogenase (an enzyme that converts UDP-glucose into UDP-glucuronic acid (Kakizaki et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019). Previous work has shown that 4-MU inhibits the production of UDP-glucuronic acid (UDP-GlcA) (Galgoczi et al . 2020), a key substrate for HA production, and the expression of hyaluronan synthases (HASs), UDP-glucose-pyrophosphorylase (an enzyme for the biosynthesis of UDP-glucose) and UDP-glucose-dehydrogenase (an enzyme that converts UDP-glucose into UDP-glucuronic acid (Kakizaki et al .…”
Section: Introductionmentioning
confidence: 99%
“…4-MU is a known inhibitor to HA synthesis (Nagy et al 2015;Nagy et al 2019). Previous work has shown that 4-MU inhibits the production of UDP-glucuronic acid (UDP-GlcA) (Galgoczi et al 2020), a key substrate for HA production, and the expression of hyaluronan synthases (HASs), UDP-glucose-pyrophosphorylase (an enzyme for the biosynthesis of UDP-glucose) and UDP-glucose-dehydrogenase (an enzyme that converts UDP-glucose into UDP-glucuronic acid (Kakizaki et al 2004;Kultti et al 2009). Interestingly, UDP-GlcA is also a substrate for the synthesis of CS, as well as some other GAGs including dermatan and heparan sulphates.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 It was observed that 4-MU can also attenuate the mRNA expression of HASes. 27 The enzymatic degradation of HA is mediated by hyaluronidases (HYAL) in combination with β-glucuronidase and β-N-acetylglucosaminidase. The most important is the action of HYAL1 and HYAL2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the metabolism of cells changes after the inhibition of HA synthesis by, for example, 4‐methylumbelliferone (4‐MU), which depletes the cytosolic pool of UDP‐GlcUA 25,26 . It was observed that 4‐MU can also attenuate the mRNA expression of HASes 27 …”
Section: Introductionmentioning
confidence: 99%
“…4-MU is available as a spasmolytic, over-the-counter drug in several European countries (named "hymecromone"). It was shown that 4-MU is a specific inhibitor of the HA synthesis in multiple cell lines, including fibroblasts from various primary tissues [24][25][26][27], keratinocytes [28], melanoma and pancreatic cancer cells [29,30]. Moreover, the effect of 4-MU has been shown in certain in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%